Trauma symptoms of sexual abuse reduce resilience in children to give 'no' replies to misleading questions. (1st January 2021) - Gudjonsson, Gisli; Vagni, Monia; Maiorano, Tiziana; Giostra, Valeria; Pajardi, Daniela
Abstract: The aim of the study was to investigate whether the extent of sexual trauma symptoms was negatively associated with 'no' answers to misleading questions after negative feedback. The participants were 180 children aged between 7 and 17 years who were suspected victims of sexual abuse. All children completed the Gudjonsson Suggestibility Scale (GSS 2), a non-verbal IQ test, and The University of California at Los Angeles Child/Adolescent Reaction Index for post-traumatic stress (UCLA-PTSD-RI-5). The findings showed that trauma symptoms, and to a lesser extent impaired source memory recall, were significantly associated with children's inability to give 'no' answers after negative feedback. The more severe the trauma, the greater the vulnerability. No such findings were found for 'don't know' and 'direct explanation' answers. The type of abuser (Intrafamilial versus Extrafamilial) did not add incrementally to the variance in 'no' answers suggesting that the impact of type of offender in terms of family links has no independent effect on 'no' answers and its effects are mediated by other factors, mainly the severity of the trauma symptoms. A 'cognitive-interpretative' model of emotional processing best explains the current findings of a relationship between trauma symptoms and 'no' answers after negative feedback.